Analisis Kompleksitas Ruang dan Waktu Terhadap Laju Pertumbuhan Algoritma Heap Sort, Insertion Sort dan Merge dengan Pemrograman Java - Rizki Rizkyatul Basir (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2020)
The role of the algorithms in software or programming is very important, so it is necessary to understand the basic concepts of the algorithm. Study the implementation and performance of the sorting process using heap sort, insertion sort and merge sort algorithms. The research method for the first stage, the three algorithms are implemented to sort the numbers made by the user, in the second stage the source code for the three algorithms is changed to be able to sort randomly generated numbers with as many numbers as the request from the user. To find out how well the performance in sorting the data, then in the last stage the three algorithms sort random numbers with a predetermined vulnerable number and then the results are compared. Experiments that have been carried out and based on the analysis, heap sort is one of the data sorting methods that are classified as having a high speed, where the complexity and speed of the sorting time needed for the sorting process uses insertion sort and merge sort algorithms which show less consistency in the complexity of time and space. Based on the results of tables and data on the amount of data, shows that the heap sort algorithm gives a very consistent processing time in increasing the processing time to the amount of data.